Assessment of Groundwater Contamination Hazard by Nitrate in Samas Area, Bantul District, Yogyakarta, Indonesia - Thilavanh Souvannachith; Doni Prakasa Eka Putra; Heru Hendrayana (Journal of Applied Geology, 2017)
Groundwater resource is an essential for various purposes in Bantul district, Yogyakarta Special Province, Indonesia, especially on Poncosari village where the water supply are depending on shallow groundwater resources. On this village, most of the houses using dug wells to provide their water needs and applying inappropriate on-site sanitation system, however there are also difference land uses. This condition increase the hazard of groundwater contamination by fecal coli bacteria and nitrate. Therefore, this research aims in term of three main objectives: ﬁrstly, to know the level of nitrate concentration in groundwater, secondly, to assess groundwater vulnerability and thirdly, to assess the level of groundwater contaminant hazard. Hydrogeology observation was conducted and 47 water samples (44 groundwater samples and 3 surface water samples) were collected from different land use type and analyze for nitrate (NO 3) content. Methodology used to assess the groundwater vulnerability was Simple Vertical Vulnerability method and the groundwater contamination hazard built based on the combination of groundwater vulnerability and nitrate loading potential map. Results show that groundwater concentrations of nitrate range from 0.09–74.80 mg/L and the highest concentration found in the settlement area. Assessment of groundwater vulnerability reveals three areas of moderate, moderate high and high classes of vulnerability due to shallow groundwater and the sandy dominated overlying material in the study area. Combination of groundwater vulnerability and nitrate loading potential map indicated that groundwater contaminant hazard of nitrate range from low to high class. High class of hazard located in the settlement area, and low hazard of nitrate contamination found in the irrigated rice ﬁeld area